Professional adaptation of female teachers in the procreation and menopausal periods - Poraj, Grażyna (Menopause Review/Przegląd Menopauzalny, 2009)
Objectives: The publication presents the characteristics of professional adaptation of female teachers in the procreation and menopausal periods. An attempt was made to ascertain whether menopause modifies their evaluation of work factors and success expectancy, whether it has influence on the level of their professional burnout as well as their job satisfaction and the satisfaction of life in general. Material and methods: 311 teachers in the 26-60 age range from the urban environment of the city of Łódź were examined. Fifty-nine women in the procreation period and 56 women in the menopausal period were selected from the whole group of teachers. Methods used in the research were: KNS Hope and Success Questionnaire, MBI Maslach Burnout Inventory, AOP Sheet to estimate work factors and job satisfaction and the general satisfaction of life. Results: In the first stage of the research a comparison of the outcomes of the teachers from the two control groups was made. No significant differences were revealed as far as success expectancy, evaluation of work factors and the level of burnout are concerned. Therefore a cluster analysis was applied. Three groups of teachers were distinguished due to their specific features and they were named as: ”unstable” (93 women), ”frustrated” (74 women) and ”adapted” (144 women). The results were compared and the analysis showed that the groups differ from one another in their success expectancy, their evaluation of work factors and also the level of burnout. Conclusions: Individual psychological qualities of the women are important resistance resource and it’s the qualities that mainly determine the teachers’ professional adaptation in different periods of life.